2022
DOI: 10.1021/jacs.2c05953
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis and Antigenicity Evaluation of Shigella dysenteriae Serotype 10 O-Antigen Tetrasaccharide Containing a (S)-4,6-O-Pyruvyl Ketal

Abstract: Shigella is the second most common etiologic pathogen responsible for childhood acute diarrhea. An anti-Shigella vaccine is still eagerly awaited due to the increasing drug resistance of this pathogen. The Shigella O-antigen is a promising vaccine target. To identify the immune epitopes of the glycan, the first total synthesis of Shigella dysenteriae serotype 10 O-antigen tetrasaccharide containing a (S)-4,6-O-pyruvyl ketal was completed. The 1,2-trans-β-glycosylation & C2 epimerization and conformational lock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 97 publications
(157 reference statements)
0
8
0
Order By: Relevance
“…To determine the specificity of glycoconjugates‐elicited IgG antibodies, a glycan microarray was constructed for screening with seven oligosaccharides ( 22 — 28 ) from different organisms, including D‐mannose, N ‐acetyl‐D‐galactosamine (GalNAc), ( S )‐4,6‐ O ‐pyruvylated D‐mannose, disaccharides, trisaccharides and phosphate‐ribosyl‐ribitol (Figure S8). [ 5,35 ] There was almost no cross‐reaction of the post‐immune sera with these oligosaccharides, which confirmed the specificity of these antibodies.…”
Section: Resultsmentioning
confidence: 54%
“…To determine the specificity of glycoconjugates‐elicited IgG antibodies, a glycan microarray was constructed for screening with seven oligosaccharides ( 22 — 28 ) from different organisms, including D‐mannose, N ‐acetyl‐D‐galactosamine (GalNAc), ( S )‐4,6‐ O ‐pyruvylated D‐mannose, disaccharides, trisaccharides and phosphate‐ribosyl‐ribitol (Figure S8). [ 5,35 ] There was almost no cross‐reaction of the post‐immune sera with these oligosaccharides, which confirmed the specificity of these antibodies.…”
Section: Resultsmentioning
confidence: 54%
“…115,117,[121][122][123][124] Similarly, the choice of hydroxyl protecting groups impacts the synthesis and the order of manipulation is essential for a successful synthesis. [125][126][127][128][129][130] Permanent protecting groups, 131,132 such as benzyl ethers (Fig. 4) stay in place throughout the synthesis and are removed after assembling the target structure.…”
Section: Glycan Connectivitymentioning
confidence: 99%
“…dysenteriae serotype 10 O-antigen in a stereoselective manner. 165 Additionally, corresponding (R)-4,6-O-pyruvylated and non-pyruvylated tetrasaccharides, as well as (S)-4,6-O-pyruvylated mannose, were also synthesized and analyzed for their antigenicity through glycan microarray screening. The results indicated that the tetrasaccharide repeating unit is a crucial antigenic epitope of the Sh.…”
Section: Vaccine Against Acinetobacter Baumanniimentioning
confidence: 99%
“…Very recently, Yin and co-workers accomplished the first total synthesis of the tetrasaccharide of Sh. dysenteriae serotype 10 O -antigen in a stereoselective manner . Additionally, corresponding ( R )-4,6- O -pyruvylated and non-pyruvylated tetrasaccharides, as well as ( S )-4,6- O -pyruvylated mannose, were also synthesized and analyzed for their antigenicity through glycan microarray screening.…”
Section: Semi- and Fully Synthetic Carbohydrate-based Antibacterial C...mentioning
confidence: 99%